2012
DOI: 10.1021/jo3023507
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Thermal Ring-Contraction of Cyclic Hydroxamic Acid Derivatives

Abstract: Cyclic hydroxamic acids can undergo a thermal ring contraction after an in situ triflation. High yields of ring-contraction products are obtained with DBU when the migrating carbon is a methylene, while best results are obtained with Et(3)N for the migration of quaternary carbons. In some cases, the regiochemical outcome of the reaction can be controlled by changing the base. This novel thermal rearrangement complements a similar but photochemical rearrangement of N-mesyloxylactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The singlet states minimize to highly strained, protonated, unsaturated lactams. In contrast, Lesard et al ,, demonstrated alkyl migrations resulting in synthetically useful ring contractions of N -chlorolactams and related derivatives (i.e., potential nitrenium ion precursors). An example of these is provided in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The singlet states minimize to highly strained, protonated, unsaturated lactams. In contrast, Lesard et al ,, demonstrated alkyl migrations resulting in synthetically useful ring contractions of N -chlorolactams and related derivatives (i.e., potential nitrenium ion precursors). An example of these is provided in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Nitrenium ions can be produced through several methods, including solvolysis of N -chloramines and oxidation of amines using hypervalent iodonium salts. However, these routes can also produce stable products from concerted reactions in addition to those from true nitrenium intermediates. Therefore, a photochemical route was chosen for the present study.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We envisaged two ways to circumvent this problem. First, we could use our second-generation ring-contraction methodology, namely, the photochemical rearrangement of N -mesyloxylactams: the yields of rearrangement products are invariably higher, and no parent lactam or radical-derived products were ever isolated in these cases . The caveat with this solution is that it is not yet possible to directly and efficiently oxidize lactams to cyclic hydroxamic acids .…”
Section: Resultsmentioning
confidence: 99%
“…Secondary amides or lactams could not contain the necessary functionalities for the rearrangement to occur (eq 2). Recently, we have added a unique complement to this list of reactions: the photochemical and/or thermal rearrangement of N -activated lactams 6 to give N -heterocycle 7 or a new lactam 8 , depending on the carbon that migrates (Scheme ). , This ring-contraction reaction complements the Schmidt-type rearrangements because it converts lactams 6a – c , thus secondary amide derivatives , to N -heterocycle 7 or 8 , and it is unique because its mechanism, though not yet completely understood, is different, perhaps involving a high-energy N -acylnitrenium ion . Notably, the Beckmann rearrangement (a ring-expansion reaction) and our ring-contraction together constitute a formidable sequence capable of transforming in three steps a cycloalkanone ( 9 ) into an N -heterocycle of the same ring size ( 11 ) with retention of the stereochemistry on either side of the starting carbonyl 9 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%